Perspectives about Spiritual Care in Pharmacy Practice: A Community-based Survey - Paul Gavaza; Bhaktidevi M. Rawal; Elizabeth Johnston Taylor (University of Minnesota Libraries Publishing, 2023)
Background: Addressing religious and spiritual needs are important components of holistic healthcare. Little is known about the general public's perspectives about pharmacists providing spiritual care (SC). Objectives: To explore how community members perceive, experience, and desire pharmacist-provided SC. Method: IRB approval was obtained for this observational, cross-sectional study. Adults receiving COVID-19 vaccinations at an immunization clinic completed an investigator-designed 33-item online survey. The survey measured respondents' perspectives about and experiences with pharmacist-provided SC, as well as demographic characteristics. Results: Of the respondents (n = 261), 57% were female and 46% were Hispanic/Latino. Most (59%) agreed that their religion/spirituality would be important to them if they were ill; 64% also agreed that it would be helpful for a pharmacist to know about patients' religious/spiritual beliefs pertaining to their healthcare, and 60% agreed that pharmacists should provide SC to patients who request it. While 96% indicated that they had never talked to a pharmacist about a spiritual or religious matter related to their health or medication, 96% also indicated that no pharmacist had asked to pray with them. These results are contextualized perhaps by the finding that 76% reported having no professional relationship with a pharmacist. Conclusion: Respondents often reported an openness to receiving SC from pharmacists. Most respondents, however, had not received SC from a pharmacist. Future studies should be conducted to better understand patient preferences for pharmacist-provided SC.